2018
DOI: 10.1111/bcpt.13154
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and dosing regimen optimisation of lopinavir in Chinese adults infected with HIV

Abstract: Lopinavir (LPV) is a protease inhibitor (PI) for the treatment of human immunodeficiency virus (HIV) infections. Current studies on LPV are mainly focused onCaucasians, and none have investigated the population pharmacokinetics (PPK) of LPV in Chinese population. The present study aimed to develop a PPK model for oral LPV in Chinese adults who are HIV-infected. A total of 460 LPV concentrations from 174 Chinese patients who received LPV/ritonavir (LPV/r) 400/ 100 mg orally every 12 hours (q12h) were analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Acute kidney injury (AKI) is a frequent complication in about 5% of hospitalized patients with coronavirus disease-2019 (COVID- 19) and an independent risk factor for in-hospital death [1]. 43.9% of COVID-19 patients exhibit proteinuria and 26.7% hematuria, which are both independent risk factors for mortality [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute kidney injury (AKI) is a frequent complication in about 5% of hospitalized patients with coronavirus disease-2019 (COVID- 19) and an independent risk factor for in-hospital death [1]. 43.9% of COVID-19 patients exhibit proteinuria and 26.7% hematuria, which are both independent risk factors for mortality [1].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine is N-dealkylated by CYP3A4 to the biologically active metabolite desethylhydroxychloroquine and the inactive metabolites desethylchloroquine and bidesethylchloroquine [14,15]. The oral bioavailability of lopinavir is low due to its rapid metabolism mainly by CYP3A4 and it is therefore co-administered with the CYP3A4 inhibitor ritonavir [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Wang et al's study, only body weight was fixed in the covariate model (Wang et al, 2020). And in other drug studies, such as in Niu et al's study, population pharmacokinetics and dosing regimen optimisation of lopinavir in Chinese adults infected with HIV, only body weight was included into model (Niu et al, 2019). However, due to the low incidence of lymphangioma, the present study has objective difficulties in the collection of children patients, resulting in the limited number of pediatric patients with lymphangioma.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Wang et al ’s study, only body weight was fixed in the covariate model ( Wang et al, 2020 ). And in other drug studies, such as in Niu et al ’s study, population pharmacokinetics and dosing regimen optimisation of lopinavir in Chinese adults infected with HIV, only body weight was included into model ( Niu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the combination of population pharmacokinetics and Monte Carlo simulation can successfully predict and recommend the best initial dosing regimen, the method has been widely used in clinical practice (Niu et al, 2019;Ren et al, 2019;Tang et al, 2019;Wang et al, 2019b). For example, Ren et al (2019) reported population pharmacokinetics of voriconazole and optimization of dosage regimens based on Monte Carlo simulation in patients with liver cirrhosis, Niu et al (2019) reported that population pharmacokinetics and dosing regimen optimization of lopinavir in Chinese adults infected with HIV, Wang et al (2019b) reported population pharmacokinetics and initial dosing regimen optimization of cyclosporin in pediatric hemophagocytic lymphohistiocytosis patients, Tang et al (2019) reported population pharmacokinetics and dosing optimization of amoxicillin in neonates and young infants. Based on these studies, the present study was to establish a population Partial concentration values were collected in a previous study (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%